2010
DOI: 10.1590/s1677-55382010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Does tumor extent on needle prostatic biopsies influence the value of perineural invasion to predict pathologic stage > T2 in radical prostatectomies?

Abstract: Purpose: Perineural invasion (PNI) on needle prostatic biopsies (NPB) has been controversial as a marker of extraprostatic extension and consequently for planning of nerve-sparing radical prostatectomy (RP). The aim of this study was to find whether tumor extent on NPB influences the value of PNI to predict stage > pT2 on RP. Materials and Methods: This retrospective study was based on 264 consecutive patients submitted to radical retropubic prostatectomy. Their NPB were matched with whole-mount processed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The findings are very similar to a study from my Institution published in Int Braz J Urol (1). We found that tumor extent on needle biopsies influences the predictive value of PNI for pathologic stage > pT2 (pT3a and/or pT3b) on radical prostatectomies.…”
Section: Editorial Commentsupporting
confidence: 90%
“…The findings are very similar to a study from my Institution published in Int Braz J Urol (1). We found that tumor extent on needle biopsies influences the predictive value of PNI for pathologic stage > pT2 (pT3a and/or pT3b) on radical prostatectomies.…”
Section: Editorial Commentsupporting
confidence: 90%
“…Several studies evaluated PNI in TRUS‐Bx in terms of locally advanced characteristics of tumors such as extracapsular extension (ECE) in radical prostatectomy (RP) specimens and most of them reported a significant relation. These studies defined PNI as a predictor of ECE, whereas, opposite results have also been reported in the literature .…”
Section: Introductionmentioning
confidence: 87%